Validity of the Swedish Rectal Cancer Registry for patients treated with major abdominal surgery between 1995 and 1997. (November 2013) - Jörgren, Fredrik; Johansson, Robert; Damber, Lena; Lindmark, Gudrun
Abstract Background. Founded in 1995, the Swedish Rectal Cancer Registry (SRCR) is frequently used for rectal cancer research. However, the validity of the registry has not been extensively studied. This study aims to validate a large amount of registry data to assess SRCR quality. Material and methods. The study comprises 906 patients treated with major abdominal surgery registered in the SRCR between 1995 and 1997. SRCR data for 14 variables were scrutinized for validity against the medical records. Kappa's and Kendall's correlation coefficients for agreement between SRCR data and medical records data were calculated for 13 variables. Results. For 11 variables, concerning the tumor, neoadjuvant therapy, the surgical procedure, local radicality and TNM stage, data were missing in 5% or less of the registrations; for the remaining three variables, anastomotic leakage, local and distant recurrence, data were missing in 13–38%. For the variables surgery performed or not and type of surgical procedure, no data were missing. Erroneous registrations were found in less than 10% of all variables; for the variables preoperative chemotherapy and surgery performed or not, all registrations were correct. For the variables concerning neoadjuvant therapy, local radicality according to the surgeon as well as the pathologist and distant metastasis, the false-positive or -negative registrations were equally distributed, and for the variables rectal washout, rectal perforation, anastomotic leakage and local recurrence there was a discrepancy in distribution. The correlation coefficient for 12 variables ranged from 0.82 to 1.00, and was 0.78 for the remaining variable. Conclusion. The validity of the SRCR was good for the initial three registry years. Thus, research based on SRCR data is reliable from the beginning of the registry's use.